Analysis of a New Medical Service Product's Marketing Strategy During the COVID-19 Pandemic - Pandhega, Arbert; David Erison, Egidius; Lukiyanto, Kukuh (KnE Social Sciences, 2024)
The purpose of this research was to find the right strategy for developing new medical services in PT. Erha during the COVID-19 pandemic. The study used qualitative research methods. The subjects were eight employees of PT. Erha in the Medical Service Development division. Data collection was done through semi-structured interviews by asking concept questions that were prepared. The results of this study showed that Medical Treatment in Erha had decreased during the COVID-19 pandemic. Therefore, it was necessary to develop a new medical treatment. To market this new product, a more effective digital marketing strategy was needed. Other results showed that the development of new products must adapt to current consumer conditions as well as regulations, government, and economic situations. The results of this study were also homogeneous between the informants. Keywords: COVID-19 pandemic, medical treatment, product development, strategy